Impact of Program Learning Objectives (PEO) of Diploma in Information Technology (Digital Technology) on Alumni Professional Skills - Mohamad , Afifa Hanim; Samad, Nur Hanifah A. (Tropical Scientific Journal, 2026)
Objective: This study focuses on assessing the achievement of Programme Educational Objectives (PEO) among Politeknik METrO Kuala Lumpur (PMKL) alumni four to five years post-graduation, fulfilling the requirement of Outcome-Based Education (OBE) and stakeholder involvement to meet industry needs. Research Method: This quantitative method employed a survey design using a structured questionnaire based on five established PEOs. The study involved 87 alumni from five intakes spanning December 2016 through December 2018. Findings: The research discusses the achievement of PEO 1, PEO 2, PEO 3, PEO 4, and PEO 5. The highest mean score from alumni feedback was PEO 4, at 4.59, while the highest mean score from employer feedback was PEO 1, at 4.73. The findings provide valuable insights into the continuous quality improvement of academic programs, ensuring their relevance to global employment demands and emerging technologies. Originality: This study is significant as it represents a pilot study for PMKL in evaluating alumni success within a defined post-graduation timeframe, utilizing alumni feedback to enhance program quality